SYNERGY OF PUBLIC RELATIONS IN BUILDING INSTITUTIONAL IMAGE AT AL-FARUQI ISLAMIC BOARDING SCHOOL, RIAU - Rini Setyaningsih; Fitria Novriani; Irawati (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2025)
Islamic boarding schools face major challenges in shaping a strong institutional image amid competition and technological advancement. This study aims to examine the synergy between public relations and strategic management in strengthening the positive image of Al-Faruqi Islamic Boarding School. Employing a qualitative approach through interviews, observation, and documentation, the findings reveal that public relations strategies are applied internally (communication with teachers, students, and staff) and externally (engaging the community, social media, and direct promotions such as roadshows and brochures). The use of platforms like Instagram, YouTube, and Facebook reflects a digital transformation, although management remains suboptimal. Moreover, the involvement of school leaders in public sermons serves as an effective communication tool. Regular evaluations are conducted to improve strategy implementation. The study concludes that a strategic integration between PR and management significantly enhances institutional image, community trust, and school competitiveness. Practically, the pesantren needs to improve digital media management and internal coordination to sustain its public reputation.